First identification of Sarcocystis tenella (Railliet, 1886) Moule, 1886 (Protozoa: Apicomplexa) by PCR in naturally infected sheep from Brazil - da Silva, Rodrigo Costa [UNESP]; Su, Chunlei; Langoni, Hélio [UNESP] (Elsevier B.V., 2009)
sarcocystis tenella is a dog-sheep protozoan parasite, causing a widespread enzootic muscle parasitosis and neurological disease mainly in lambs. This parasite is pathogenic to sheep and important to the economical production of sheep. The present study was initially aimed to determine Toxoplasma gondii infection and the occurrence of co-infection with other Apicomplexa parasites in 602 Brazilian sheep. Twenty of these sheep were positive with antibodies to T gondii by MAT and IFAT-IgG tests, positive with PCR-RFLP genotyping at multiple loci, and parasites were isolated from mice infected with sheep tissue samples. Two additional sheep born in Brazil, a 2-year-old female Polwarth (Ideal) sheep, a breed originated from Australia (#1), and a 1-year-old male Corriedale sheep, a breed originated from New Zealand and Australia (#2) were positive to T. gondii antibodies by serum tests, and PCR, but negative for bioassay in mice. In genotyping; at 12 loci, sheep #1 sample and #2 presented positive results only for some markers. PCR-RFLP of 18S ribosomal RNA(18S rRNA) was performed in all 22 animals to identify the possibility of co-infection of T gondii with other Apicomplexa parasites, such as S. tenella, Neospora caninum and Hammondia hammondi, resulting in a T. gondii profile for the first 20 animals and a unique genotyping profile for sheep #1 and #2, identical to S tenella The 18S rRNA PCR products(similar to 310 bp)were sequenced and blasted to GenBank database at NCBI. Both samples were identical to S. tenella 18S rRNA gene (GenBank accession number L24383-1). These results suggest the existence of co-infection of S. tenella with T gondii in ewes from Brazil (c) 2009 Elsevier B V. All rights reserved.
Keywords: Sarcocystis tenella; Toxoplasma gondii; Natural infection; Co-infection; Molecular techniques; Slaughterhouse; Human consumption